MAPPING OF THE INDIAN FISHERIES GROWTH RATE AND FISH CONSUMPTION THROUGH GIS - Singh, Ram; Sharma, Rama; Biradar, R. S. (Journal of Indian Fisheries Association, 2015)
In the present study, Indian fisheries growth rate and fish consumptionhave been analyzed through GIS mapping. The analyses were based on thestate-level fisheries data of India collected from the secondary sources.Accordingly, the paper contains one thematic map containing two layers. To achieve this, all the data have been brought into a tabular form through Microsoft Excel and then joined to Map Info Professional Version 8.0 GIS software with digitized map of India for further analysis to generate thematic maps. In this thematic map, the first Jayer represents the growth-rate of fish production for the period 1990-2004 and. the second layer represents fish consumption for the year 2003. The thematic map represented in graphic form presents inland, marine and total growth rates, and also the rural and urban fish consumption at the state levels. This study will be useful to fish traders, planners, researchers and administrators in fisheries policy formulation for sustainable development.Keywords : GIS, thematic map, digitized map, fish production